Overview of the Pediatric Endoscopy Quality Improvement Network Quality Standards and Indicators for Pediatric Endoscopy: A Joint NASPGHAN/ESPGHAN Guideline. (16th March 2022) - Walsh, Catharine M.; Lightdale, Jenifer R.; Mack, David R.; Amil-Dias, Jorge; Bontems, Patrick; Brill, Herbert; Croft, Nicholas M.; Fishman, Douglas S.; Furlano, Raoul I.; Gillett, Peter M.; Hojsak, Iva; Homan, Matjaž; et al.
ABSTRACT: Introduction: Pediatric-specific quality standards for endoscopy are needed to define best practices, while measurement of associated indicators is critical to guide quality improvement. The international Pediatric Endoscopy Quality Improvement Network (PEnQuIN) working group was assembled to develop and define quality standards and indicators for pediatric gastrointestinal endoscopic procedures through a rigorous guideline consensus process. Methods: The Appraisal of Guidelines for REsearch and Evaluation (AGREE) II instrument guided PEnQuIN members, recruited from 31 centers of various practice types representing 11 countries, in generating and refining proposed quality standards and indicators. Consensus was sought via an iterative online Delphi process, and finalized at an in-person conference. Quality of evidence and strength of recommendations were rated according to the GRADE (Grading of Recommendation Assessment, Development, and Evaluation) approach. Results: Forty-nine quality standards and 47 indicators reached consensus, encompassing pediatric endoscopy facilities, procedures, endoscopists, and the patient experience. The evidence base for PEnQuIN standards and indicators was largely adult-based and observational, and downgraded for indirectness, imprecision, and study limitations to "very low" quality, resulting in "conditional" recommendations for most standards (45/49). Conclusions: The PEnQuIN guideline development process establishes international agreement on clinically meaningful metrics that can be used to promote safety and quality in endoscopic care for children. Through PEnQuIN, pediatric endoscopists and endoscopy services now have a framework for auditing, providing feedback, and ultimately, benchmarking performance. Expansion of evidence and prospective validation of PEnQuIN standards and indicators as predictors of clinically relevant outcomes and high-quality pediatric endoscopic care is now a research priority.